Experimental Study on Deformation Law of Rectangular Roadway in Horizontal Layered Rock Mass - Dinggui Hou; Yunying Zhou; Jingxiang Wang (Advances in Materials Science and Engineering)
In order to analyze the characteristics and mechanism of roadway deformation caused by high stress in horizontal strata, a physical model with rectangular roadway was designed. The model was constructed by the so-called “Physically Finite Elemental Slab Assemblage (PFESA)” to bring about the structural effect of the deep strata. In the experiment, the vertical and horizontal pressures were increased step-by-step to simulate high stress. The deformation characteristics of surrounding rock in layered rock roadway were observed by video image and digital image correlation method (DIC). The strain and stress characteristics of surrounding rock of roadway in layered rock mass were obtained by using the strain gauge test method, and compared with the deformation characteristics. For the sake of analyzing the deformation and failure mechanism of layers, the mechanical model of layered rock structure was established, and the experimental phenomenon and mechanism were verified. Through systematic study, this paper enriches the research methods of model experiment and provides an experimental basis for practical engineering of similar conditions.